PENGELOLAAN PANTAI KEDONGANAN SEBAGAI DAYA TARIK WISATA KULINER BERBASIS MASYARAKAT DI DESA KEDONGANAN - Md. Abdi Sucipta; Solihin Solihin (Politeknik Negeri Bali, 2013)
This research shows that the Community Based Tourism (CBT) at Kedonganan beach for culinary tourism developed successfully: economic, social and culture since 2007. The Kedonganan villagers are involved from the beginning simultaneously as a part of six villages of Kedonganan. They established 24 cafes, it means every village has 4 cafes to be managed and funded by LPD as sponsor. It used to be 70 cafes since 1990 managed individually with fish market, but without any development for the villagers, and now it is with a rapid development based on CBT. The development of the ecology prosperous with the Tri Hita Karana philosophy. The data collecting are purposive sampling to submit information from the leader of the villagers